(Bio-/Cyber-/Robo-)technologically Enhanced and Designed “People” in the Most Recent Croatian Dystopian Prose - Rezo, Vladimira (Poznańskie Studia Slawistyczne, 2022)
The following paper focuses on typification and cataloguing of the various manifestations of body decorating and enhancing in selected novels and stories, and also tries to examine their meanings, what changes they bring, what attitude of the authors towards technological progress they reveal and what social/cultural phenomena and processes they reflect. The paper also questions the upgrades of the human mind and the transformations of humans into some other forms of existence. Nine contemporary dystopian novels and five short stories have been studied for the purposes of this research. The methodological framework consists of texts that question the enhancement of the human body conducted in various ways, especially through biotechnology, bioengineering, cybernetics, robotics, etc.